Analisis Peran Perempuan dalam Memanfaatkan Potensi Lokal Sebagai Alternatif Usaha di Kampung Tanjung Talok Desa Teluk Sasah Kabupaten Bintan - Andesta, Indah (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
Research involving women’s Tanjung Talok Village as the object of study aims to analyze the role of women in utilizing the local potential and can be used as business products in Tanjung Talok Village. In Tanjung Talok village, there are five local communities (groups), and each group has one effect of being developed. This study did in Tanjung Talok village from March until July 2021. Furthermore, the research uses qualitative and quantitative methods. Researchers conducted in-depth interviews, observations, and literature reviews. The data obtained were analyzed by a qualitative descriptive approach. The variable in this research is women in Tanjung Talok village who have still productive to develop a small business product. The results showed that the role of Tanjung Talok in utilizing local potential was not maximized. From a total of 104 family data, it was known that women who had businesses based on local potential were 15 women with products such as fish crackers, gamat oil, chips, peanut brittle, chili paste, and other small businesses. The role of Tanjung Talok women is maximized by having a business group with Tanjung Talok’s women to develop small Business or household products. Most women in Tanjung Talok have the skill to process those products. Marketing and packaging are challenging to create those products due to women in Tanjung Talok don’t have much talent or experience on their part. The following research has to focus on analyzing the effectiveness of the management model that will apply in Tanjung Talok village